PREDESTINATION AND ESSENISM - Tantlevskij, Igor; Svetlov, Roman (SCHOLE, 2014)
The widely spread Essenes practice of the future events prediction is likely to be based on their belief in the absolute predestination. In this light the hitherto unclarified etymology of the very term Εσσαιοι / Εσσηνοι can be traced to the Aramaic notion חשיא (pl. st. emph.)/resp. חשאין (st. abs.; sing. חשא), which is likely to be interpreted as “what man has to suffer, predestination, fortune”; this derivation appears to be relevant not only semantically, but also linguistically. The doctrine of predestination also plays the key role in religious outlook of the Qumran community, and it is considered to be one of the most fundamental arguments in favor of the Qumranites identification with the Essenes. Some Platonic-Pythagorean (not only Stoic) doctrines can be regarded as certain Hellenistic parallels to the Essenic-Qumranic conception of predestination.